Effects of IAA and kin on somatic embryogenesis and the effect of acadian marine plant extract powder content on micropropagule regeneration of the seaweed Kappaphycus striatus - Vu, Thi Mo; Nguyen, Ky Sanh; Le, Trong Nghia; Tran, Van Huynh; Tran, Mai Duc; Vo, Thanh Trung; Hoang , Nhat Uyen My; Nguyen, Thuy Phuong; Ho, Son Lam (Vietnam Journal of Marine Science and Technology, 2026)
The objective of this study was to perfect the callus culture method for propagating Kappaphycus striatus. Our research focuses on enhancing somatic embryo (SE) induction from callus and on micropropagule regeneration in SEs. To enhance the induction rate of SEs, the 16-week-old callus was transplanted into a semi-solidified PES (0.4% agar) medium supplemented with 0.5–3.0 mg.L-1 3-indoleacetic acid (IAA) and 0.5–3.0 mg.L-1 kinetin (KIN), either alone or in combination. The results showed that transplanting the callus into a PES medium containing IAA and KIN (0.5–3.0 mg L-1), either individually or in combination, significantly affected somatic embryogenesis in K. striatus. After 8 weeks of cultivation, the treatment with 1 mg.L-1 IAA + 2 mg.L-1 KIN exhibited the highest embryo induction rate (62.22 ± 5.09%) and the greatest number of SEs (182.00 ± 10.58 embryos/explant) compared to other treatments. Moreover, during the micropropagule regeneration stage, the commercial powdered extract of Ascophyllum nodosum (Acadian Marine Plant Extract Powder, AMPEP) at concentrations ranging from 5 ppm to 50 ppm was found to enhance the rate of micropropagule regeneration from SEs of K. striatus. The optimal regeneration of SEs of K. striatus into complete micropropagules occurred in an AMPEP medium at a concentration of 20 ppm. Micropropagules cultured in this medium displayed the highest survival rate (75.6 ± 5.09%), number of branches (7.67 ± 0.58 branches/micropropagule), branch length (24.7 ± 1.53; 25 ± 1.00 mm), and fresh weight (173.7 ± 8.14 mg) compared to alternative treatments.